La indisciplina en el proceso de enseñanza aprendizaje educación básica media - Amores Garzón, María Judith (2017)
The present research project had its focus on the indiscipline in the process of teaching learning in middle primary education, it was developed with the purpose of examining its factors, components and consequences to determine the impact it has on the development of the educational process. The research problem lies in the increase of acts of indiscipline that have originated in the institution due to the confluence of elements that originate the behaviors of indiscipline within the classroom. The methodology applied contains a qualitative approach since it is a socio-educational problem, which was complemented by the bibliographical research that allowed gathering the scientific information of diverse sources to deepen in the study of the indiscipline and the process of teaching learning. Field research that focuses on obtaining data directly from the actors involved in the educational issue as they are teachers and practitioners. The technique that has been used for data abstraction is the survey and the instrument used the questionnaire, which is structured with closed questions and multiple selection that have allowed the identification of the perception of teachers and students regarding indiscipline and its influence In the teaching-learning process. From the application of the survey technique, the following results obtained were teachers talk to parents when the student has undisciplined behavior within the classroom, it is deduced that the less involvement of the student in the problem, the greater the recurrence of situations of indiscipline. The students consider that every day there are acts of indiscipline in the classroom, so it is evident that the recurrence of indiscipline is high. It is recommended that teachers implement immediate action strategies to eradicate indiscipline, focused on the student to improve their participation and awareness of the need to keep order and discipline in the classroom. Promote actions that help reduce the recurrence of acts of indiscipline within the classroom, such as educational talks, inclusion of dynamics at the beginning or end of the class, among others.